2019
DOI: 10.4038/jsc.v10i2.21
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of mango (<em>Mangifera indica</em> L.) latex and anatomy of latex canals

Abstract: Mango latex is important in the mango industry due to its antimicrobial properties and the burn it causes on the harvested fruits. The present study is a qualitative investigation of the composition of mango latex, the variation in latex volumes among three selected local mango cultivars and the anatomy of fruit pedicel and peel that contain the latex canal system. According to the biochemical tests, the aqueous phase of mango latex contained moderate amounts of carbohydrates and reducing sugars which are disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Large latex channel openings were seen at and below the abscission zone close to the fruit. High volume of latex spurts out through these channels after detaching the pedicel from the fruit [82]. Latex canals are seen as large perforations in the fruit peel reaching the outer pulp [34,82].…”
Section: Mango Pedicel and Abscission Microscope Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Large latex channel openings were seen at and below the abscission zone close to the fruit. High volume of latex spurts out through these channels after detaching the pedicel from the fruit [82]. Latex canals are seen as large perforations in the fruit peel reaching the outer pulp [34,82].…”
Section: Mango Pedicel and Abscission Microscope Imagesmentioning
confidence: 99%
“…High volume of latex spurts out through these channels after detaching the pedicel from the fruit [82]. Latex canals are seen as large perforations in the fruit peel reaching the outer pulp [34,82]. After cutting the Keitt mango pedicel 2 cm away from the abscission zone, it was cauterized at 35°C, showing latex channels (Figure 4a).…”
Section: Mango Pedicel and Abscission Microscope Imagesmentioning
confidence: 99%
“…Karunanayake, 34 Krishnapillai and Wijeratham, 16 and Saby John et al 35 indicated that mango sap is highly acidic in nature with a pH of 4.3and therefore injures/ scorches the fruit skin/peel when in contact, thus rendering the fruit unappealing/unsightly. According to Barman et al, 21 the onset and severity of mango sap burn injury increased up to ripening during storage at ambient temperatures.…”
Section: Sap Burn Injury Scores Fruit Pulp Colour Consistency Skin/peel Colour Mean Scores and Total Soluble Solids (Tss) Content In Relamentioning
confidence: 99%
“…The resin has been found to contain triterpenes, mainly cycloartanes [ 13 ], and cardols have also been reported [ 4 ]. The latex, on the other hand, contains monoterpenes with typical raw mango aroma [ 16 , 17 ], cardols [ 18 20 ], carbohydrates, and small amounts of proteins [ 21 , 22 ]. No triterpenes have been detected in latex, although several detailed studies have been carried out.…”
Section: Introductionmentioning
confidence: 99%